A Review on Pollutants Found in Drinking Water in Sub-Sahara African Rural Communities: Detection and Potential Low-cost Remediation Methods - Fouda-Mbanga, Bienvenu Gael; Seyisi, Thulethu; Nthwane, Yvonne Boitumelo; Nyoni, Bothwell; Tywabi-Ngeva, Zikhona (Industrial and Domestic Waste Management, 2023)
Water is the most essential substance that supports various life mechanisms. It is a fundamental and necessary requirement for mankind and all other living creatures on the planet. Therefore, daily drinking water should be clean, readily available, sufficient, and free from harmful substances. However, in many rural areas, most sources of drinking water are assumed to be safe for human consumption, but this is not always the case. This work aims to provide a review of pollutants found in the drinking water of Sub-Saharan rural communities and explore potential low-cost remediation methods. The assessment of water pollutants and their remediation methods has been the primary focus of research for several years. Additionally, the World Health Organisation has established various minimum standards regarding the concentration of common pollutants in water. This review presents the major sources of water, the origin of contaminants, the different types of pollutants, and remediation methods to enhance the current knowledge in the field of rural drinking water contaminants.